Challenges relating the acquisition of the distinctiveness for colour per se trade mark registration - Labeja, Alise (Riga Graduate School of Law, 2019)
Colour per se trade mark registration has always been a relatively complex process especially assessing the mandatory requirement of distinctiveness. The abolition of the previously mandatory necessity for graphic representation has promoted greater attention to the issues relating the distinctiveness aspects. The examination of existing courts practice and the case analysis is used in order to estimate main challenges relating the acquisition of the distinctiveness for colour per se trade mark registration. The main issue that hinder the acquisition of distinctiveness is the competition aspects, thus courts are not interested to encourage excessive colour monopolization in order to avoid any aggravation of the competition environment
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; Trade marks